FEASIBILITY STUDI MASYARAKAT PENERIMA PROGRAM BANTUAN PANGAN NON TUNAI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT INDONESIA - Indirawati, Surachmi; Azizah, Dwi Waliyatul; Budiawan, Budiawan; Sumanti, Sumanti; Delu, Abidah R. (ITB AAS Indonesia Surakarta, 2024)
Poverty in Indonesia is currentely a very pressing problem. One way the government is trying to reduce the poverty rate in Indonesia is by implementing the BPNT program. Non-Cash Food Assistance Program, aimed at poor communities with the criteria of beneficiary families. This research looks at the feasibility of the BPNT Program in improving community welfare in Rejo Binangun Vilage. The research method used in the research uses quantitative methods with descriptive analysis. The population in this study was 320 KPM, the Solvin formula was used to obtain a more specific sample size of 76 KPM. Previous research related to BPNT only focused on poverty allevation, therefore this research tries to see the feasibility of the BPNT Program in improving community welfare. The results of the research found that there was a difference in BPNT distribution, which was originally in the form of basic necessities, now in the form of cash. Furthermore, in regression testing, the result showed that there was a positive and significant influence on community welfare. Therefore, it can be said that the Non-Cash Food Assistance program is still feasible in improving community welfare in terms of access to food, nutritional quality, family welfare, family finances and benefits for KPM recipients.